Cover Picture: A General and Efficient Synthesis of 2‐Pyridones, 2‐Quinolinones, and 1‐Isoquinolinones from Azine N‐Oxides (Asian J. Org. Chem. 12/2016). Issue 12 (7th December 2016) - Wang, Dong; Zhao, Junjie; Wang, Yuxi; Hu, Jianyong; Li, Linna; Miao, Longfei; Feng, Hairong; Désaubry, Laurent; Yu, Peng
Abstract : Hydroxyl N‐heteroarenes, which remain challenging to synthesize via current methods, are present in numerous natural products and are ubiquitous building blocks in medicinal chemistry. A novel, general and practical approach for the synthesis of hydroxyl N‐heteroarenes from the corresponding N ‐oxide precursors has been established. This method employs bromotripyrrolidinophosphonium hexafluorophosphate (PyBrop) as an activating agent and sodium acetate/water as the base/nucleophile combination. The mechanism of the reaction has been elucidated by isotopic labeling experiments. More information can be found in the Communication by Dong Wang, Peng Yu et al. onpage 1442 in Issue 12, 2016 (DOI:10.1002/ajoc.201600430 ).